Research on Hologram Based on Holographic Projection Technology. (20th May 2022) - Li, Yan; Yu, Qun; Wu, Yu; Wei, Changcheng
Abstract : In recent years, holographic projection technology has been integrated into the real society, which brings a new visual experience to people and meets their high requirements for audiovisual experience. With the development of holographic technology, the hologram from holographic technology has also attracted people's attention. The application of holograms in the fields of art, science, and technology conforms to the trend of the times and will become an indispensable part of people's life in the future. In this paper, it mainly studies the hologram to analyze its algorithm and production process and its application prospects.